Analisis Pengukuran Produktivitas di PT Powertek Industri Mandiri dengan Metode Omax (Objective Matrix) - Fashal Ariyanda; Efta Dhartika Priyana; Moh. Jufriyanto (G-Tech: Jurnal Teknologi Terapan, 2024)
PT Powertek Industri Mandiri is a company engaged in the procurement of goods and services of servo services, inverters (VFD) and panels, in the implementation of internships at PT Powertek Industri Mandiri experienced obstacles in terms of productivity, many were not resolved. Therefore, the OMAX method is used to help solve productivity problems, especially in the service area. The data used in the analysis includes the results of interviews and data on completed and uncompleted work orders. From the results of the analysis using the OMAX method, the results can be concluded from the initial objective, namely The best productivity is estimated to occur in August 2022, which is 750 and the lowest is 400 in March and December, and data from the TLS system shows that quality and quantity affect the company's productivity